Effectiveness of assistive computer technology (act) for enhancing basic language skills among students with hearing disabilities - Mazlan, Nurul Hijja; Mohd Daud, Shaffe; Ayob, Ahmad Fauzi (Universiti Putra Malaysia Press, 2010)
It is well-documented that deaf children are often delayed in language development compared to their hearing peers. However, invention of assistive computer technology (ACT) gives deaf students the opportunity to enhance their language skills and immerse on new and more interactive virtual learning environment. The purpose of this paper is to review the potential and effectiveness of ACT for improving language skills and learning outcomes among deaf students. The review is organized into two major sections which reflect the theoretical framework to date, as well as dialogic reading interventions and technology interventions on the deaf’s written language. Many researchers conclude that dialogic reading interventions have yielded significant improvement on deaf students’ language development and ACT has demonstrated efficacy in enhancing language skills among students with hearing disabilities. Educational considerations in planning computer-based dialogic reading intervention for students with deafness in Malaysia are deliberately discussed for future practitioners and educators.